Tarekat Naqsyabandiyah di Pontianak (Study Naskah Nukilan Tarekat Naqsyabandiyah) - Samidi khalim (Balai Penelitian dan Pengembangan Agama Semarang, 2009)
This manuscript studies using historical approach and hermeneuticanalysis. As for who becomes the object of study is the script tariqatNaqsyabandiyah (NTN), one script that provides information aboutteaching in Naqsyabandiyah tariqat in Pontianak. Tariqat Naqsyabandiyah,becoming known by the people of West Kalimantan, Pontianak, especiallysince the Dutch colonial period (ca. 1919), after the return of Ismail Jabalfrom Mecca. Manuscript NTN is a private collection H. Zahry AbangAbdullah Al Ambawwi, one of the Indigenous Cultural Council board Melayu(MABM) West Kalimantan. Manuscript provides clues about the teachingof the doctrine Naqsyabandiyah tariqat Repentance, Remembrance andMakrifat Concept.Keywords: Tariqat Naqsyabandiyah, Manuscript, Dhikr, Repentance